PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA DAKWAH: INDRA HOTMIAN - Hotmian, Indra (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2024)
This article discusses the use of social media as a means of dakwah (Islamic preaching). In the current modern era, social media represents the advancement of information and technology, prompting an analysis of how social media is utilized, particularly in the context of dakwah. The research problem in this study focuses on understanding how social media is utilized as a tool for dakwah, given the popularity of social media phenomena among the public. The applied method in this research is qualitative, employing a literature review approach involving data collection through understanding and studying theories from various relevant literature on the research topic. The literature review process comprises four stages: equipment preparation, bibliography compilation, time management, and reading and note-taking of research materials. The research findings indicate that dakwah is an activity involving the dissemination of Islam through invitations and calls, and one of the effective approaches is through media. Social media is considered the most effective tool for dakwah activities. However, dakwah through social media should adhere to the ethics and norms applicable on those platforms. Thus, the benefits derived from worship activities through dakwah on social media can genuinely be realized. In practical terms, this research can contribute to further studies, especially considering that dakwah continues to be carried out by Da'i (Islamic preachers) who need to adapt to the evolving social conditions, technology, and increasingly advanced and modern information trends. Consequently, Da'i are expected to adapt and compete in facing technological developments by enhancing their skills and knowledge.